Tunable quantum cascade lasers for midinfrared spectroscopic sensing - Li, Jinghao (Nanyang Technological University, 2024)
Many gases of interest exhibit strong absorptions within the Mid-infrared (Mid-IR) region, spanning from 2.5 to 25 µm. To enable high-sensitivity spectroscopy, a robust coherent source in this range is required. Quantum cascade lasers (QCLs) possess inherent intersubband transitions that allow for tunability of emission wavelengths across the entire Mid-IR spectrum through band structure engineering. As a result, they have become valuable tools for precise optical sensing in various applications, including environmental monitoring, homeland security, and safe production. Particularly, there is a demand for single-mode lasers that can be tuned over a wide wavelength range without mode hopping, as they hold promise for detecting and distinguishing distinct components in chemical mixtures through quantitative analysis on absorption spectra. Another requirement for optical sensors is good portability, allowing for multi-location detection in remote areas. Therefore, the development of a monolithic tunable QCL with a wide continuous tuning range free of external setups is highly desirable. In this thesis, we propose a design of slot waveguide QCL arrays. A proof-of-concept ten-emitter array enables mode-hop free tuning soely with currents over 71 cm^-1 around 10 µm at 300 K. To make the array a feasible source in practical spectroscopic applications, we propose a novel method using an aspherical lens and fine-tuned mini mirrors, which combine the beams from a five-element slot QCL array with a transmission efficiency of 92% to the far-field. Based on this beam combined tunable QCL array, we develop a portable sensor that integrates the modules of drivers, optical sensing, and signal processing in a box. It can simultaneously detect ammonia and ethylene gases at different concentrations through software control and AI model-based spectra analysis. Finally, we design a novel tunable QCL based on coupled ring resonator filters. The fabricated device achieves a quasi-continuous tuning range of ~ 18 cm^-1 around 7.4 µm by varying heatsink temperature.